KEMAMPUAN MENYIMAK TEKS CERITA RAKYAT PADA SISWA KELAS X SMA NEGERI 5 PONTIANAK - Paisal, Asep; Salem, Laurensius; Ramdani, Deden (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstractâ€œThe Ability To Listen To Folklore Text On Students Of ClassÂ X SMA Negeri 5 Pontianakâ€ This study aim is to describe the ability in listening to folklore text on students of class X SMA Negeri 5 Pontianak. The method used in this research is descriptive method and quantitative research form. Based on the results of the calculation of percentage in the data analysis, it can be concluded that the percentage of students' ability to determine the character and the characterization on the folklore text is 87% that labeled as